Exploring Maternal Knowledge and Stimulation Practices in the Development of Children with Down Syndrome - Endang Susilowati; Arum Meiranny; Ghina ‘Aisy; Tri Winarni; Agustini Utari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Down syndrome is a common genetic disorder in children, with rising cases in Central Java—from 210 in 2020 to 650 in 2024—a 63% increase in three years. Children with Down syndrome face developmental challenges across all domains including motor, sensory, cognitive, language, and social aspects. Parental involvement, especially mothers, plays a crucial role in optimizing developmental outcomes. However, observations at POTADS Semarang indicate limited maternal knowledge and inadequate stimulation practices. This study aims to explore maternal knowledge and behaviors related to developmental stimulation in children with Down syndrome at POTADS Semarang.. Methods: This analytic survey employed a cross-sectional approach conducted in August 2024 with 75 mothers meeting the inclusion criteria. Data were collected using a structured and closed questionnaire. Ethical approval was obtained from the Research Bioethics Committee of Sultan Agung Islamic University, and informed consent was obtained from all participants. Results: The study found a significant correlation between maternal knowledge and stimulation behavior. Statistical analysis showed a 2-tailed significance value of 0.003 (<0.05). Most mothers (44%) had moderate knowledge of child development stimulation, and the majority (53.3%) demonstrated negative behaviors in providing age-appropriate developmental stimulation. Conclusion: Among the 75 respondents, 40 (53.3%) were over 35 years old, 52 (69.3%) were unemployed, and 58 (77.3%) had completed secondary education. Spearman Rank test analysis yielded a p-value of 0.003 (<0.05), indicating a significant relationship between maternal knowledge and behaviors regarding developmental stimulation. Mothers with moderate and low levels of knowledge were more likely to exhibit negative stimulation behaviors.